SYSTEM OF PRE-UNIVERSITY TRAINING "SCHOOL - MEPHI" - I. V. ТSVETKOV; D. Y. PRAVNIK (Moscow Polytechnic University, 2017)
The article describes the experience of the National Research Nuclear University "MEPhI" of engineering competences formation in the pre-university training system. The authors show how the research component can enhance physical and mathematical and technological education. The paper considers the implementation of the primary and secondary education programs (Pre-Universitary, engineering classes, AtomClasses, distance education in Network school), analyzes the methods of selection and support for students who have shown creativity and interest in engineering.